Case report: acute myocardial infarction in the setting of acute transcatheter aortic valve thrombus - Hebbo, Elsa; Khoury, Alessandro El; Iskandarani, Dounia; Sawaya, Fadi (Frontiers in Cardiovascular Medicine, 2023)
We describe a case of valve thrombosis and a subsequent thromboembolic event within only 10 days of transcatheter aortic valve implantation (TAVI). Postprocedural anticoagulants are not standard of care medications post-TAVI in patients without atrial fibrillation. Valve thrombosis is an indication to initiate anticoagulation to resolve and prevent further thrombus.